Responsabilidad de los administradores en las Entidades Sin Ánimo de Lucro (ESAL). (2019)
Non-Profit Organizations (NOPs) were created to benefit vulnerable communities; their proper functioning is their administrators’ responsibilities. Nevertheless, how far does the responsibility of an administrator of this type of entity go? This article analyzes the regulations that govern commercial firms and NPOs, as well as the scope, particularities and interpretations that frame the responsibility of the administrators of Non-Profit Organizations. Regulating NPOs and their representatives is an example case in which analogy offers solutions to regulatory gaps and helps to harmonize the branches of law for the organizations’ benefit and their purpose.